Performance evaluation of heating tower heat pump systems over the world. (15th April 2019) - Huang, Shifang; Ye, Yunyang; Han, Xu; Zuo, Wangda; Zhang, Xiaosong; Jiang, Li
Highlights: The models of the heating tower heat pumps (HTHPs) are developed and validated. A large-scale performance evaluation of the HTHPs in 869 locations are carried out. The distributions of seven performance indices are presented through color maps. The HTHPs have excellent performance in the warm and mixed climate zones. Abstract: Heating tower heat pumps (HTHPs) are proposed as an alternative to the conventional heat pumps. However, lacking performance evaluation of the HTHPs in different regions limits their applications worldwide. To address this issue, this paper carries out a large-scale comprehensive performance evaluation of the HTHPs in 869 typical locations. These locations are in the warm, mixed, and cool climate zones, where buildings need both cooling and heating supply. Seven performance indices are adopted, including the annual coefficient of performance (COP), COP in cooling season, COP in heating season, regeneration ratio, number of unsatisfactory hours, matching degree of heat pump, and matching degree of heating tower. The performance evaluation of the HTHPs is conducted by the processes of location selection, building load calculation, system sizing, simulation, and evaluation. The results show that the HTHPs have excellent performance in the warm and mixed climate zones, where the average annual COPs are 4.67 and 3.68, respectively. The HTHPs are also applicable in the cool climate zone with an average annual COP of 3.11. The distributions of all the performance indices are presented through color maps, and the results are analyzed considering the air temperature and relative humidity data of the locations.